Endoscopic retrograde cholangiography via a permanent access loop - Kaplan, Mustafa; Dişibeyaz, Selçuk; Ödemiş, Bülent; Parlak, Erkan; Öztaş, Erkin; Gökbulut, Volkan (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The aim of this study was to investigate the indications, technical and clinical success, and complications of the endoscopic retrograde cholangiography (ERC) via a permanent access loop (PAL). Materials and Methods: Twenty patients who underwent ERC through PAL between 2009 and 2017 were included in this study. The technical success was described as achieving access to the bile ducts through PAL and the clinical success was described as the clinical and laboratory improvement of the patients after the procedure. Results: The study was performed with 20 patients. The median follow-up duration was 24 months (3-96) and the median number of ERC sessions was 3.9 (1-10). The most common ERC indications through PAL were stones (40%) and cholangitis (30%). In 16 patients (75%), anastomotic or branched strictures were observed. The improvement of strictures via intermittent stenting and dilatation was observed in 6 patients, but no improvement was observed in 5 patients. The treatment of those 5 patients continues. In this study, the technical success was 100% and clinical success was 85%. While no mortality due to PAL-mediated ERC was observed, free wall perforation was seen in one patient who was referred to surgery. Conclusion: PAL-mediated ERC procedure is a technique with high technical and clinical success and low complication rate in patients who require frequent percutaneous procedures and those with difficult access to the biliary tract.